Controlling Shareholder and Tax Avoidance: Family Ownership and Corporate Governance - Masripah, Masripah; Diyanty, Vera; Fitriasari, Debby (Universitas Prasetiya Mulya, 2015)
The objective of this study is to analyze the entrenchment effect of controlling shareholder on tax avoidance, as well as looking at the role of family ownership, commissioner effectiveness, audit committee effectiveness and external audit quality. This research is a quantitative research using fixed effects model. Sample of this research is 70 firms with an observation period of 2010 until 2013. This study finds that the entrenchment effect of controlling shareholder has negative effect on tax avoidance. Other test results show that when a family is the controlling shareholder, entrenchment effect of controlling shareholder do not affect on tax avoidance. Board of commissioner and committee effectiveness proved to weaken the relationship between entrenchment effect of controlling shareholder and tax avoidance. However, the role of external quality audit does not prove to weaken the relationship between the entrenchment effect of controlling shareholder and tax avoidance.